Home mechanical ventilation. (6th April 2011) - Wise, Matt P; Hart, Nicholas; Davidson, Craig; Fox, Rik; Allen, Martin; Elliott, Mark; Winter, Bob; Morgan, Mike; Shovelton, Helena; Meadowcroft, Robert; Campbell, Jane; Finlay, Ilora
Abstract : National registries are needed to reduce variations in care and improve patient safety